IMPLEMENTING FLIPPED CLASSROOM MODEL WITH PEER GROUP TO STRENGTHEN EFL UNIVERSITY STUDENTS' WRITING ACHIEVEMENT - Zuhra, Intan; Agustisa, Mutia; Darwis, Muhammad (Premise: Journal of English Education and Applied Linguistics, 2025)
This study was designed to assess students' writing achievement in the third semester of the Syiah Kuala University Paragraph Writing Course in 2021. This study used a quasi-experimental design. Pre-tests, post-tests, and questionnaires were employed as the research instruments. The data were analysed quantitatively. The results indicate that the mean score of the post-test for the experimental group (83.52) is higher than that of the control group (68.76).Furthermore, the percentage of questionnaire results showed that 27.3% strongly agree and 51.1% agree that this teaching model motivates students in learning writing. It can be concluded that there is a significant difference in the writing achievement of students between the experimental and control groups. In other words, the Flipped Classroom Model with Peer Group is an effective teaching model. Hence, the implementation of the Flipped Classroom Model with Peer Group in teaching writing could improve students' learning results and increase students' writing motivation.